How to make employees love their work? - I Nyoman Resa Adhika (Philippine Social Science Journal, 2025)
To address turnover rates in food catering MSMEs—which peaked at 24.35% in 2023—this study utilized a descriptive survey design to examine the impact of workload, job stress, and work motivation on turnover intention. Statistical analysis revealed that while increased workload and job stress significantly heighten the intention to leave, work motivation has no observed effect. Consequently, the findings suggest that businesses must prioritize balanced task distribution and stress management programs to mitigate burnout and fatigue. Future research should expand the scope beyond the catering industry and explore additional variables, such as job satisfaction and work experience, to provide a more comprehensive understanding of retention dynamics.